Food aid, external trade and domestic markets implications for food security in Darfur - Dorosh, Paul A.; Subran, Ludovic (SAGE Publications, 2011)
In the last decade, internal conflict has greatly hindered market transactions across regions of Sudan, especially transactions between Darfur and the rest of Sudan. Food aid has helped to offset not only the absence of commercial inflows of grain, but also reductions in Darfur’s cereal production. This article explores the determinants of cereal prices in Sudan utilising a simple partial equilibrium framework for wheat and sorghum, the country’s two main food staples. We also present econometric evidence on the lack of integration of sorghum markets between Darfur and central Sudan, along with quantitative estimates of the impacts of food aid on market prices in the region. The article concludes with a discussion of national food policy and the paradox of simultaneous commercial exports and large-scale food aid imports of sorghum.